John Hersey revisited - Sanders, David, 1926- (Boston : Twayne Publishers, 1990)
Presents an update of an earlier study of John Hersey's fiction and analyzes how The Call (1985) casts new light on his previous writing.
Includes bibliographical references (p. 117-124) and index.
Young Adult.
Young Adult
Keywords: Hersey, John, -- 1914- -- Criticism and interpretation; Hersey, John, -- 1914-